The guest ebook - Cline, Emma (2023)
NATIONAL BESTSELLER • A young woman pretends to be someone she isn’t in this “spellbinding” ( Vogue ), “smoldering” ( The Washington Post ) novel by the New York Times bestselling author of The Girls . “Under Cline’s command, every sentence as sharp as a scalpel, a woman toeing the line between welcome and unwelcome guest becomes a fully destabilizing force.”— The New York Times A BELLETRIST BOOK CLUB PICK • VULTURE ’S INAUGURAL "BEACH BOOK READS" BOOK CLUB PICK • LONGLISTED FOR THE PEN/FAULKNER AWARD A BEST BOOK OF THE YEAR: The New Yorker, Time, NPR, The Washington Post, Financial Times, Harper’s Bazaar, Elle, Vogue, Glamour, Newsweek, Good Housekeeping, Slate, Time Out, Chicago Public Library, Electric Lit, Bookreporter “Alex drained her wineglass, then her water glass. The ocean looked calm, a black darker than the sky. A ripple of anxiety made her palms go damp. It seemed suddenly very tenuous to believe that anything would stay hidden, that she could successfully pass from one world to another.” Summer is coming to a close on the East End of Long Island, and Alex is no longer welcome. A misstep at a dinner party, and the older man she’s been staying with dismisses her with a ride to the train station and a ticket back to the city. With few resources and a waterlogged phone, but gifted with an ability to navigate the desires of others, Alex stays on Long Island and drifts like a ghost through the hedged lanes, gated driveways, and sun-blasted dunes of a rarefied world that is, at first, closed to her. Propelled by desperation and a mutable sense of morality, she spends the week leading up to Labor Day moving from one place to the next, a cipher leaving destruction in her wake. Taut, propulsive, and impossible to look away from, Emma Cline’s The Guest is a spellbinding literary achievement.